International Trade, Prosperity and Inequality in Globalization (2021)
This paper purpose is to make a description and a critical discussion about some key trends in the world trade of goods and services, and economic inequality during the last decades in the globalization context. With this aim, we explain some key processes underlying this evolving capitalist phase. From there, we point out the main virtuous processes but also economic problems characterizing the evolution of the world economy during the last decades. The result of this dynamic has been the perpetuation of various types of inequalities, and the permanence of a large set of social groups mired in poverty and tied to territories generally exploited by the grasps of transnational capital, whose own discourses and worldviews end up being invisible by issuers who proclaim themselves as universal.